Severe Adenovirus Pneumonia Requiring Extracorporeal Membrane Oxygenation Support in Immunocompetent Children - Chen, Xuefei; Lv, Jianhai; Qin, Lu; Zou, Chaochun; Tang, Lanfang (Frontiers in Pediatrics, 2020)
Objective To highlight severe adenovirus pneumonia in immunocompetent patients by analysis of severe adenovirus pneumonia associated with acute respiratory distress syndrome in whom extracorporeal membrane oxygenation (ECMO) support is required. Methods Pediatric patients with adenovirus pneumonia and ECMO supports in our hospital from February 2018 to May 2019 were retrospectively analyzed, and having 100 common adenovirus pneumonia children as a control. Results A total of 8 patients, including 4 boys (50.0%), were enrolled. They were previously immunocompetent with a median age of 31 months. They were admitted as persistent fever and cough for more than one week. Median time prior to development of respiratory failure requiring intubation and invasive mechanical ventilation was 5 days. Venoarterial ECMO support as rescue ventilation was instituted after a median time of 24.5 hours of conventional mechanical ventilator support. The median duration on ECMO support was 9 days and mechanical ventilation was 14 days, respectively. Six patients (75%) were recovered and 2 (25%) died. Median length of stay in ICU and hospital were 27.5 days and 47.5 days respectively. Conclusion The promising outcomes of our cases suggested that ECMO support for rescue ventilation may be considered when symptoms deteriorated in adenovirus pneumonia patients, and may improve outcome. However, sequelae of adenovirus pneumonia and ECMO-related complications should also be taken into account.